Intrachromosomal Recombination within the vsp Locus of Mycoplasma bovis Generates a Chimeric Variable Surface Lipoprotein Antigen - Lysnyansky, Inessa (American Society for Microbiology, 2001)
A family of 13 related but divergent vsp genes was recently found in the chromosome of the bovine pathogen Mycoplasma bovis. The vsp genomic locus was shown to undergo high-frequency rearrangements and to mediate phenotypic switching of variable lipoprotein antigens (Vsps) on the mycoplasma cell surface. Here we report that the vsp gene repertoire is subject to changes. Genetic analysis of M. bovis clonal isolates displaying distinct Vsp phenotypes showed that an intergenic recombination event between two closely related members of the vsp gene family, the formerly expressed vspA gene and the vspO gene, led to the formation of a new chimeric and functional vsp gene, vspC. The 5′ end of the recombination event was identified within the highly conserved vsp-upstream region, while the 3′ end was localized within the first repetitive domain (R(A)1) present in both vspA and vspO structural genes. As a result, the vspC gene is an embodiment of the following domains: an N-terminus-encoding region linked to the highly conserved vsp-upstream region provided by the vspO gene; and a C-terminus-encoding region and the more distal and divergent vsp-upstream region acquired from the vspA gene. The generation of chimeric genes encoding surface antigens may provide an important element of genetic variation and an additional source of antigenic diversification within the mycoplasma population.